Employment, education, and family: Revealing the motives behind internal migration in Great Britain - Thomas, Michael J. (Population space and place, 2019)
Distinctions between internal migration and residential mobility are often formed with reference to assumed differences in motivation, with migration typically linked to employment and educational motives and shorter distance mobility to housing and family. Using geocoded microdata, this article reveals how employment‐led migration represents only a minority share (≈30%) of total migration events over 40 km. Family motives appear just as important, even at distances ≥100 km, with the desire to live closer to non‐resident family/friends being the most frequently cited family submotive. Estimated propensities to undertake employment and educational‐related migration fit very closely to predictions of human capital models of migration, being highest among young, residentially flexible and highly educated individuals. Migrants citing family‐related motives are disproportionately drawn from midlife and later‐life phases, with family shown to be a key motive among migrants with care‐related needs (e.g., parents with children) or access to fewer resources (e.g., social renters and low educational attainment).